(9x-1)(3x+9)=0

Simple and best practice solution for (9x-1)(3x+9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x-1)(3x+9)=0 equation:


Simplifying
(9x + -1)(3x + 9) = 0

Reorder the terms:
(-1 + 9x)(3x + 9) = 0

Reorder the terms:
(-1 + 9x)(9 + 3x) = 0

Multiply (-1 + 9x) * (9 + 3x)
(-1(9 + 3x) + 9x * (9 + 3x)) = 0
((9 * -1 + 3x * -1) + 9x * (9 + 3x)) = 0
((-9 + -3x) + 9x * (9 + 3x)) = 0
(-9 + -3x + (9 * 9x + 3x * 9x)) = 0
(-9 + -3x + (81x + 27x2)) = 0

Combine like terms: -3x + 81x = 78x
(-9 + 78x + 27x2) = 0

Solving
-9 + 78x + 27x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3'.
3(-3 + 26x + 9x2) = 0

Factor a trinomial.
3((-3 + -1x)(1 + -9x)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(1 + -9x)' equal to zero and attempt to solve: Simplifying 1 + -9x = 0 Solving 1 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -9x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -9x = 0 + -1 -9x = 0 + -1 Combine like terms: 0 + -1 = -1 -9x = -1 Divide each side by '-9'. x = 0.1111111111 Simplifying x = 0.1111111111

Solution

x = {-3, 0.1111111111}

See similar equations:

| 3(1/4)p=2(1/2) | | 6(x-1)+46=-2x | | -6.5(4p+6)-1.4(3p-5)=0 | | 50+4y-22=13y-14-3y | | (31/4)p=21/2 | | 1/5n=12 | | -3-(5-5p)=0 | | -3(-2*x+4)-(x-6)=y | | f(m)=20-0.25m | | 69-5x=4x+18 | | 3y-10=5x+22 | | x^2=-13 | | -17x-20=-14x+70 | | -7/3(y-12)-1/6y=0 | | 3/4x-3/2=6 | | -7/3(y-12)-1/6y | | 4x+9=3x+17 | | 3x+7=2x+15 | | 5x^3/2-35=100 | | -177=9*n | | 11x-3=3x+21 | | 9x+18=27 | | 5x-35=100 | | 6x-5=31-2x | | 24-3x=56+2x | | 3x-4(7x+3)=5x+7(9x-10) | | 5.59+55.9=111.8 | | -17-(-40)=x/2 | | X=2(-2)+6 | | X*13-110=x*6-12 | | 5(5c-1)-3=23c+2 | | 3x/2+5=16x-11 |

Equations solver categories